Nurses’s Burnout and Anxiety about Risk of Infection toward Quality of Life during the COVID-19 Outbreak - Ina Martiana; Hendra Dwi Cahyono (Poltekita : Jurnal Ilmu Kesehatan, 2022)
The novel coronavirus disease (COVID-19) is a global pandemic in all over countries. Nurses as frontline worker who taking care of infected patients and have high risk of being infected by COVID-19. This pandemic affects physical and psychological conditions of nurses. The aim of this study was to identify the correlation between nurse’s burnout and risk of infection anxiety toward quality of life. This study used descriptive cross-sectional design. A total of 102 participants joined this research. The participants were nurses who work in COVID-19 isolation room. The data collecting process has done by online. The participants filled informed consent and questionnaire by online questionnaire. The study was assessed by Professional Quality of Life-5 (ProQOL-5), C-19ASS (COVID-19 Anxiety Syndrome Scale), and CBI (Copenhagen Burnout Inventory). This study was analyzed using non-parametric Kruskal Wallis. The results of the study were 56.9% of respondents had a high level of anxiety, 50% of them experienced burnout. There is a significant relationship between length of work and quality of life of CS (p value = 0.048). There is also a relationship between burnout and STS quality of life (p value = 0.033). The pandemic situation is being fluctuated and people adapted to it. The anxiety and burnout feeling was also change anytime. The more nurses being prepared, the lower burnout, and having good quality of life. The good teamwork to support and feeling of being appreciate give good quality of life for nurses.